Broken Homes Examined Through Epistemology, Axiology, and Ontology - Melatika Kurnia Devi; Wiryo Nuryono (Journal of Social Research, 2026)
This study addresses the increasing prevalence of broken homes and their multifaceted impacts on children and family systems. Globally and in Indonesia, high divorce and separation rates have raised concerns about children's psychological, educational, and social development. The study aims to explore broken homes from philosophical perspectives—ontology, epistemology, and axiology—to provide a holistic understanding of their effects and implications for counseling and family support. A qualitative literature review was conducted, analyzing national and international academic journals, books, theses, and proceedings related to family disruption, child development, and guidance counseling. A purposive sampling technique was used to select 50–70 relevant sources, and data were extracted using a structured template, ensuring validity through expert review and reliability via cross-checking and consensus. NVivo 12 software facilitated thematic coding and analysis, linking observed phenomena to structural, cognitive, and value-based dimensions. The findings indicate that broken homes disrupt family structures (ontology), shape children's knowledge and perceptions of relationships (epistemology), and affect ethical and value frameworks (axiology). Children often experience insecurity, loneliness, and emotional challenges, although resilience and positive adaptation can occur with proper guidance. The study concludes that philosophical perspectives enrich understanding of broken homes and recommends future empirical and longitudinal research to develop effective interventions that support children's well-being, resilience, and ethical development.